Avaliação das concentrações plasmáticas de cortisol e progesterona em vacas nelore (Bos taurus indicus) submetidas a manejo diário ou manejo semanal - Maziero, Rosiára Rosária Dias [UNESP] (2012)
This study evaluates the plasma concentration of progesterone and cortisol in cows submitted to daily or weekly handling. For this experiment, seven primiparous or multiparous Nelore cows (Bos taurus indicus) were monitored for 21 days (experiment 1) and 9 weeks (experiment 2) through rectal palpation and ultrasonographic examination of the female reproductive tract, as well as jugular venipuncture. Plasma concentration of progesterone and cortisol (ng/mL) was determined by radioimmunoassay from blood samples collected from jugular vein on the differently handling experiments. For experiment 1, the plasma concentration of progesterone ranged from 0.13 to 4.42 ng/mL, however, there were no differences in experiment 2 (0.17 to 1.2 ng/mL; p > 0.05). Plasma concentration of cortisol showed values between 10-50 ng/mL in experiment 1 and 8.3 to 62 ng/mL in the experiment 2. There were correlations between cortisol and progesterone in the experiment 2 (r = 0.909; p 0.05) but not in the experiment 1 (r = 0.03; p > 0.05). The handling procedures used in experiments were able to induce stress in the treated animals.